Membangun Jiwa Kepemimpinan Pada ANak SD YPK Klasaman 1 Kota Sorong - Muskita, Susana M. W.; Lahallo, Fensca; Ferdinandus, Arce Y.; Pakpahan, Ratna R.; Rupilele, Frits G. J.; Madina, La Ode; Maniburi, Marice Y.; Sanar, Firda S.; Lewaherilla, Patricia J. O. (Yayasan Kajian Riset Dan Pengembangan Radisi, 2025)
This community service activity aims to build leadership spirit in early childhood at SD YPK Klasaman 1 Sorong City. Leadership spirit is one of the important aspects that need to be developed from an early age in order to form individual characters who are responsible, confident, and able to collaborate. The methods used in this activity are mentoring, simulation, question and answer methods, which are designed to develop basic leadership skills such as communication, decision making, empathy, and courage. The results of this activity show that the participating children have high enthusiasm and have improved in understanding leadership values. This program has a significant positive impact in building the character of early childhood and is the first step to instill leadership in the school environment. Hopefully, this activity can provide long-term benefits for the character development of the younger generation in Sorong City.